EFEKTIFITAS PENGGUNAAN MODEL PEMBELAJARAN TREFFINGER TERHADAP KEMAMPUAN BERPIKIR KRAETIF SISWA DI KELAS X SMA NEGERI 2 - Cesilia Tampubolon (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to describe the effectiveness of using treffinger learning model on students’ creative thinking ability at the tenth grade students of SMA Negeri 2 Siabu. This research was conducted by applying experimental method (pretest post test one group design) with 25 students as the sample and they were taken by using random sampling from 100 students. Observation and test were used in collecting the data. Based on the data analysis, it was found that: (a) the average of using treffinger learning model was 3.8 (very good category) and (b) the average of students’ creative thinking ability before using treffinger learning model was 24.95 (poor category) and after using treffinger learning model was 83.60 (very good category). Furthermore, based on inferential statistic by using paired sample ttest, the result showed the significant value was less than 0.05 (0.000 < 0.05). It means, using treffinger learning model was effective used on students’ creative thinking ability at the tenth grade students of SMA Negeri 2 Siabu.